Public Service Interpreting and Translation: Moving Towards a (Virtual) Community of Practice - D’Hayer, Danielle (Meta, 2012)
Following many battles, Public Service Interpreting and Translation (PSIT) is gradually evolving towards professionalisation. Wherever it is practiced, common issues have been identified: defining the profession, providing interpreting services for rare or minority languages, educating stakeholders, moving from training to education, and last but not least interpreting and translation quality. The lack of funding for PSIT courses within the current financial context is forcing stakeholders to work differently. The community of practice model can help PSIT stakeholders share resources and knowledge beyond the traditional boundaries set by courses, schools or countries. New technologies such as virtual conference tools and shared repositories are the essential “missing link” towards the progress of PSIT education. PSIT stakeholders need to join forces and pool efforts towards a constructive and innovative dialogue that would enhance the profession. Some forms of PSIT, such as legal interpreting and translation, have already broken barriers and gained professional recognition. However, PSIT should include all forms of PSIT contexts, including the medical or local government. Finally, once fully defined, PSIT and conference interpreting for spoken and sign languages could finally come together under the Interpreting profession umbrella. This is the achievable ultimate aim when working as communities of practice, small or large, language specific or generic, face to face or virtual.